Peneraparan Sistem Perjanjian Kerja Waktu Tertentu di Indonesia - Aditya Pane; Mimi Atika Rahma; Ranti Nadila (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
An employment agreement as a preliminary means before an employment relationship takes place, must be implemented as well as possible, in the sense of reflecting justice for both the employer and the worker, because both will be involved in an employment relationship. The purpose of this research is to find out the form and content of a fixed-term work agreement in its implementation and how the protection for workers/laborers in a fixed-term work agreement is implemented according to Law Number 13 of 2003 concerning Employment. The research method used is a qualitative method. It is necessary to emphasize the limitations that must be fulfilled by those who make employment agreements, especially employers, so that material regarding conditions that are very detrimental to the worker is taken into account, for example the existence of clauses in the term of the employment relationship and other materials that are often not realized will be very detrimental, especially to the recipient of the work. .